Comparison of Anti-inflammatory Effect between Intracameral Triamcinolone Acetonide and Topical Dexamethasone after Phacoemulsification - Muhammad Moin, Asif Manzoor (Pakistan Journal of Ophthalmology, 2018)
Objective: To compare the role of single dose intracameral injection of triamcinolone acetonide versus topical dexamethasone to control post-operative inflammation after phacoemulsification. Study Design: Randomized controlled trial. Place and Duration of Study: Ophthalmology Department, Lahore General Hospital, Lahore, from March 2015 to August 2015. Methodology: A total of 60 patients of 40 ? 70 years of age of either gender undergoing phacoemulsification for cataract were included. Selected patients were placed randomly into two groups by using lottery method. Group A patients were given 1 mg/0.1 ml triamcinolone acetonide into anterior chamber at the end of surgery and no topical steroids were given post-operatively. Group B were not given intracameral injection but topical dexamethasone eye drops were given 4 hourly for one week and then four times a day for 4 weeks. Outcome variable was control of post-operative inflammation, which was noted at day 1, 7 and 28. Results: Mean age of patients in group A was 58.63 ? 7.30 years and in group B was 56.63 ? 5.87 years. Out of 60 patients, 34 (56.67%) were males and 26 (43.33%) were females. The male to female ratio was 1.3:1. The difference in efficacy between the two groups was statistically non-significant. Conclusion: Single dose Intracameral injection of triamcinolone acetonide controls post-operative inflammation after phacoemulsification without the use of any eye drops and is equally as effective as topical dexamethasone for post-operative inflammation Keywords: Cataract, inflammation, Phacoemulsification, Triamcinolone.